Prevalence and etiology of dermatomycoses in Rajshahi, Bangladesh - Neela, Farzana Ashrafi (Journal of Life and Earth Science, 2011)
Dearmatomycoses are very common infections caused mainly by dermatophytes. A total of 1186 patients ranging from 1-60 years of age were surveyed for dermatomycotic infections in Rajshahi, Bangladesh. Specimens for mycological investigations were confirmed by microscopic examinations in 817 cases and the causative agents were isolated and cultured in 70 positive cases. The highest prevalence of dermatomycosis was of Tinea corporis (63%) followed by T. pedies (15%), T. capitis (12%) and T. unguium (8%). Trichophyton and Microsporum were the major etiological agents followed by Epidermophyton. This study also showed that there is a great variation in the severity of different types of dermatomycoses at different months of the year. Key words: Dermatophytes; dermatomycoses; Tinea DOI: 10.3329/jles.v2i2.7501 J. Life Earth Sci., Vol. 2(2) 75-78, 2007